ANALYSIS OF THE GENERIC STRUCTURE OF NEWS ITEM ON THE MOST VIEWED VOICE OF AMERICA (VOA) LEARNING ENGLISH VIDEOS IN FEBRUARY 2016 - Saparena, Ayun Bekti; Areni, Galuh Kirana Dwi; Bahri, Seful (ELT Forum: Journal of English Language Teaching, 2018)
This final project focuses on the analysis of the generic structure and lexicogrammaticalfeatures of news item text found in the most viewed Voice of AmericaLearning English videos in February 2016. The main purposes of this study are toidentify how the construction of generic structure and significant lexico—grammatical features of news item are applied in Voice of America (VOA) LearningEnglish videos based on news item text structure analysis. This study is descriptivequalitative research. The research data are the transcripts of ten most viewed videossorted during February 2016. The result of analysis of the generic structure showsthat all texts implemented the generic structure of news item text. All of them usedthe appropriate standard of generic structure of news item text stated by Gerot andWignell. The result of analysis of the lexico-grammatical feature shows that all ofthe elements realized in the texts are well structured. All the texts have beenarranged and written based on the complete requirements of lexico-grammaticalfeature of news item text stated by experts. However, the researcher found somedeviations in the text related the use of generic structure and lexico-grammaticalfeatures of news item. Based on the explanation above, the researcher concludes thatnews item text found in Voice of America Learning English videos generally havecompleted standard generic structure and language features of news item text.